MgCl2 center dot 4(CH3)(2)CHOH: a new molecular adduct and super active polymerization catalyst support - Thushara, K. S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
A new molecular adduct, MgCl(2 center dot)4(CH3)(2)CHOH, has been synthesized and characterized for structural aspects and demonstrated for super active ethylene polymerization activity with TiCl4 to ultrahigh molecular weight polyethylene in high yield.